The microbial metabolite isovaleric acid aggravates gelatinase-mediated periodontal tissue destruction via the NF-κB signaling pathway - Zheng, Huiling; Tu, Ying; Ning, Xinjie; Guo, Qiang; Ren, Biao; Xie, Jing; Liu, Chengcheng (Journal of periodontology (1970), 2025)
Isovaleric acid, an important short-chain fatty acid, can be generated by subgingival microbial fermentation of a leucine-rich diet, such as Porphyromonas gingivalis. This study aimed to explore the impact of isovaleric acid on the destruction of periodontal tissues and to investigate the underlying mechanisms. The level of isovaleric acid in the saliva of clinical subjects was measured via mass spectrometry. Isovaleric acid local injection models in 5-week-old male Sprague Dawley rats and an isovaleric acid treatment model of human periodontal ligament stem cells (hPDLSCs) were established to explore the effect of isovaleric acid on periodontal tissue destruction and uncover the underlying mechanisms. Our study revealed that individuals with gingivitis and periodontitis presented significantly higher salivary levels of isovaleric acid than healthy controls. Local injections of isovaleric acid aggravated periodontal tissue damage and alveolar bone loss in rats. Moreover, isovaleric acid amplified the levels and activities of gelatinases, a process facilitated through the activation of NF-κB (nuclear factor kappa-B) signaling. Suppression of the NF-κB pathway significantly reduced the isovaleric acid-induced increase in gelatinases. Our findings demonstrate that isovaleric acid aggravates the destruction of periodontal tissue by modulating the levels and activities of gelatinases via the NF-κB signaling pathway both in vitro and in vivo. Periodontitis is a chronic inflammatory disease characterized by the destruction of periodontal tissues, with oral bacteria as the progressive frontier. Isovaleric acid, an important short-chain fatty acid, is a substance produced by oral bacteria during the breakdown of protein-rich foods. By comparing saliva samples from healthy individuals and patients with periodontal diseases, we found that isovaleric acid levels were 2‒3 times higher in patients with inflamed or damaged periodontal tissue. In this study, we assessed the effects of isovaleric acid on periodontal tissues by injecting isovaleric acid into the gums of rats and treating human periodontal cells with isovaleric acid. We found that isovaleric acid worsened periodontal tissue damage and accelerated bone loss. This process worked through NF-κB signaling pathway activation, which increased the activity and expression of gelatinases, enzymes that break down periodontal tissues. These findings increase our understanding of the possible involvement of isovaleric acid in the development of periodontitis. Targeting isovaleric acid metabolism may provide new approaches for the treatment or prevention of periodontitis.